Endobronchial mucosal nodular lesions in allergic bronchopulmonary aspergillosis. (2020) - Nihashi, Fumiya; Hiramatsu, Toshiya; Uto, Tomohiro; Sato, Jun; Imokawa, Shiro; Suda, Takafumi
Abstract: Bronchoscopic findings often show mucoid impaction in patients with allergic bronchopulmonary aspergillosis (ABPA); however, endobronchial mucosal nodular lesions have not been reported. We herein present the first such case of a 52-year-old woman with ABPA with endobronchial mucosal nodular lesions. The endobronchial lesions were located in the orifice of the mucoid impaction, and disappeared after 4 weeks of treatment with prednisolone and itraconazole. Aspergillus fumigatus was cultured from bronchial lavage fluid collected from the site of mucoid impaction. Based on these clinical findings, we speculate that the bronchial lesions were caused by an inflammatory and allergic reaction to Aspergillus antigens.